Technology in Elementary School Science Learning Media and Resources: A Literature Review with Implications for BiMbeLcc - Asthania Asthania; Poppy Yullia Murtiningtyas; Lukmanul Hakim (MASI Mandiri Edukasi, 2025)
The rapid development of science and technology has significantly influenced the educational sector, particularly science learning at the elementary school level. This study aims to examine the role of technology in elementary science learning media and learning resources, with implications for fourth-grade learners at the BiMbeLcc tutoring institution in Cilegon. The research employed a descriptive qualitative approach using a literature review method. The literature search was conducted using national databases (Sinta-indexed journals) and international databases such as Google Scholar and ERIC, covering publications from 2015 to 2024. The inclusion criteria consisted of peer-reviewed articles discussing educational technology, science learning media, and elementary education, while articles that were not focused on elementary-level learning, lacked methodological clarity, or were non-academic publications were excluded. Based on the screening and eligibility process, a total of selected articles were analyzed thematically to identify recurring patterns and key findings. The results indicate that the integration of technology in science learning media such as Canva, Kahoot, YouTube, Google Chrome, and artificial intelligence plays an important role in supporting students’ learning motivation, engagement, and understanding of scientific concepts. Technology-based learning media provide interactive, visual, and contextual learning experiences that promote student-centered learning and accommodate diverse learning styles. In addition, technology facilitates educators in designing varied and innovative learning media and enables efficient access to broader learning resources. However, the review also identifies potential challenges in technology integration, particularly the risk of students’ overdependence on technological tools, which may reduce learning independence if not properly managed. Therefore, technology should be applied selectively and responsibly in accordance with pedagogical principles. Overall, this study concludes that technology can enhance the quality of elementary science learning when integrated thoughtfully. Strengthening students’ scientific reasoning, logic, and critical thinking remains essential in the digital era to ensure that technology functions as a supportive tool rather than a substitute for meaningful learning processes.